Case report: Brincidofovir-induced reversible severe acute kidney injury in 2 solid-organ transplant for treatment of cytomegalovirus infection. Issue 44 (November 2016) - Faure, Emmanuel; Galperine, Tatiana; Cannesson, Olivier; Alain, Sophie; Gnemmi, Viviane; Goeminne, Celine; Dewilde, Annie; Béné, Johana; Lasri, Mohamed; Lessore de Sainte Foy, Célia; Lionet, Arnaud
Abstract: Rationale: Resistant cytomegalovirus-mediated infections are increasing in solid organ recipient with few available alternative treatments. Brincidofovir is an oral broad-spectrum antiviral in development for prevention and treatment of viral infection, particularly cytomegalovirus. Patients concerns: Although brincidofovir is an analogue of cidofovir, previous studies reported no renal toxicity. Diagnoses: Here, we report 2 cases of severe tubular necrosis in solid organ recipients, 1 heart and 1 kidney transplant. Interventions: Both patients received brincidofovir for the treatment of cytomegalovirus infection with mutation of UL-97. They presented an acute kidney injury without any occurrence of other clinical event such as introduction of nephrotoxic drug, graft rejection, urinary tract obstruction or infection, and calcineurin inhibitor overdosage. In each case, renal biopsy showed extended tubular necrosis. Outcomes: The discontinuation of brincidofovir led to improve renal function without other any intervention. Reintroduction of brincidofovir in case 1, due to the absence of other medical alternative, led to a new episode of acute kidney injury. One more time, renal biopsy showed tubular necrosis and patient recovered renal function after discontinuation. Lessons: To our knowledge, this is the first report of brincidofovir-mediated renal adverse event. Clinicians may be aware of this severe complication in this specific population.